2004
DOI: 10.1152/ajpendo.00326.2003
|View full text |Cite
|
Sign up to set email alerts
|

AMPK activity and isoform protein expression are similar in muscle of obese subjects with and without type 2 diabetes

Abstract: Acute or chronic activation of AMP-activated protein kinase (AMPK) increases insulin sensitivity. Conversely, reduced expression and/or function of AMPK might play a role in insulin resistance in type 2 diabetes. Thus protein expression of the seven subunit isoforms of AMPK and activities and/or phosphorylation of AMPK and acetyl-CoA carboxylase-beta (ACCbeta) was measured in skeletal muscle from obese type 2 diabetic and well-matched control subjects during euglycemic-hyperinsulinemic clamps. Protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
49
1
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 43 publications
7
49
1
6
Order By: Relevance
“…Furthermore, it was recently shown that skeletal muscle mitochondrial capacity for oxidative phosphorylation in Asian Indians with type 2 diabetes is the same as in nondiabetic Indians [39]. Similarly, we have shown that AMPK or ACC status does not appear to be implicated in type 2 diabetes in accordance with previous studies [40][41][42] and at odds with others [43]. While obese participants without type 2 diabetes do not show defective mitochondrial respiration, they do have a significant increase in citrate synthase activity and significantly reduced AMPK levels.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, it was recently shown that skeletal muscle mitochondrial capacity for oxidative phosphorylation in Asian Indians with type 2 diabetes is the same as in nondiabetic Indians [39]. Similarly, we have shown that AMPK or ACC status does not appear to be implicated in type 2 diabetes in accordance with previous studies [40][41][42] and at odds with others [43]. While obese participants without type 2 diabetes do not show defective mitochondrial respiration, they do have a significant increase in citrate synthase activity and significantly reduced AMPK levels.…”
Section: Discussionsupporting
confidence: 92%
“…Because ACC2 is predominantly expressed in muscle and heart (42), our measurement of malonyl-CoA likely reflects the activity primarily of ACC2. Previous reports did not find decreased AMPK activity in insulin-resistant human muscle (43)(44)(45), whereas skeletal muscle from obese rats did display decreased AMPK and increased ACC activities (46). In studies with obese rat muscle, Lessard et al (46) demonstrated that the decrease in AMPK activity and phospho-ACC levels were normalized after rosiglitazone treatment, similar to what we observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In this regard, previous studies have reported no change in skeletal muscle AMP kinase activity in type 2 diabetic subjects compared with control subjects. However, in two of these previous studies, the control group and type 2 diabetic groups were either both lean (44) or both obese (45), so that no differences in adiposity existed between the control and type 2 diabetic subjects. Thus, these results do not disagree with our own data because we found that differences in obesity correlated more closely with decreased AMP kinase activity than did the presence of diabetes.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, AMPK activity in skeletal muscle from patients with type 2 diabetes appears to be intact. Basal activity is similar to matched controls (13,34), and the enzyme can be activated normally by acute exercise (13) and metformin in vivo (13,35) and by AICAR in vitro (36). These reports also suggest that skeletal muscle insulin resistance is unlikely to be initiated by dysfunction of the AMPK trimer.…”
Section: Discussionmentioning
confidence: 62%